Nilai Kata dalam Novel Emprit Abutut Bedhug Karya Suparto Brata - Indrayanto, Bayu; Tukiyo, Tukiyo; Anisa, Ike (Universitas PGRI Semarang, 2025)
The research entitled Word Values in the Emprit Abutut Bedhug Novel by Suparto Brata formulates three research problems, namely forms, functions and word values in the Emprit Abutut Bedhug novel by Suparto Brata. The word forms in Emprit Abuntut Bedhug's novel by Suparto Brata are in the form of adjectives, phrases, and clauses, dominated by word forms in the form of phrases. Emprit Abutut Bedhug's novel by Suparto Brata is a neat novel using a variety of Javanese languages both in ngoko and krama. While the value of the word discussed there are six, among others: the value of the word inappropriate, the value of the word that has a high value, the value of the word that has a bad value, the value of the word that has a rough value, the value of the word that has a funny value, and the value of the word that has a level value or high degree. For the value of words that have a funny value in the novel Emprit Abuntut Bedhug by Suparto Brata, it is not found and the word value that has a high level or degree is dominant.